Taking, begging, or waiting for the floor: students' social backgrounds, entitlement and agency in classroom discourse. Issue 2 (4th March 2023) - Orner, Aviv; Netz, Hadar
ABSTRACT: This paper presents an ethnographic study analyzing the influence of students' social backgrounds on students' entitlement and agency in relation to floor rights. Classroom interactions were video-recorded, and interviews were conducted in a socially diverse fifth-grade in Israel. Descriptive statistics and micro-analyses of participation patterns reveal a discursive mechanism whereby students from more privileged backgrounds, endowed with higher senses of entitlement and agency, use floor obtaining strategies, such as calling out and begging, which increase their learning opportunities, often at the expense of their less privileged peers. The research contributes to expanding our understanding of the mechanisms of educational injustice, advancing us towards their rectification. As such, the study may be of interest to both educational researchers as well as practitioners.